Analysis Of The Use Of Fruit Dice And Bar Chart Media On Learning Outcomes In Data Collection For Fifth-Grade Students At SD Fontein II, Kupang City - Nahak, Kristina E. Noya; Wunga, Michael W. Dapa; De Jesus, Laurdes T.; Anabokay, Ria; Snae, Dortia; Efron H. Otu (Jurnal Scientia, 2024)
In elementary school education, mathematics learning is crucial for an individual's ability to understand, use, and interpret mathematics in everyday life. Mathematics should be implemented in a fun learning environment. In mathematics learning, students should be introduced to gain knowledge related to the characteristics found in an object or a collection of objects. In mathematics learning, there is a statistics material that includes the sub-material of data collection. Data collection is an important material in mathematics. The data collection process includes collecting and measuring the necessary information according to the objectives. In learning, media is needed as an intermediary to convey information quickly. Such as fruit dice media which are shaped like a cube and have six sides. In addition to fruit dice media, bar chart media are also used to present data from the results of data collection. However, this is often overlooked by teachers in learning. This study aims to analyze the use of fruit dice and bar chart media to improve student learning outcomes in mathematics learning on data collection material in class V SDN Fontein 2 Kupang City. This type of research is qualitative with a descriptive method. Data collection was carried out through observation, interviews, and student knowledge tests through the questions given. The number of students in this study was 25 people. The use of fruit dice and bar chart media begins by dividing students into groups, where students will roll fruit dice 20 times and collect the results of the throws in the form of a bar chart. The results showed that the use of fruit dice and bar chart media can increase students' activeness and participation in the learning process. This can be seen from the average student score of 70 to 80. This shows that fruit dice and bar chart media have succeeded in improving student learning outcomes in mathematics on data collection material. In addition, this media also managed to create a fun, enjoyable, and interactive learning atmosphere, which attracts students' interest and motivation to learn.